2018
DOI: 10.1186/s12864-018-4974-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing to detect the potential role of long non-coding RNAs in bovine mammary gland during the dry and lactation period

Abstract: BackgroundIt is known that long non-coding RNAs (lncRNAs) play an important role in various biological processes, including cell proliferation, differentiation and apoptosis. However, their functions and profiles in lactation cycle of dairy cows are largely unknown. In this study, lncRNA-seq technique was employed to compare the expression profiles of lncRNAs and mRNAs from Chinese Holstein mammary gland in dry and lactation period.ResultTotally 3746 differentially expressed lncRNAs (DELs) and 2890 differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 69 publications
(80 reference statements)
2
41
1
Order By: Relevance
“…These characteristics indicate the functional diversity of lncRNAs, which may perform different important physiological regulatory roles in mammary gland development and lactation. Other studies, such as those conducted on bovines, have attempted to identify and characterize the expression of lncRNAs in peak, late and dry lactation stages [23,24], and lncRNAs, as an important posttranscriptional regulators, participate widely in the regulation pathways related to the development and lactation of mammary glands. Therefore, an extensive investigation of the functions of lncRNAs will provideus with a clear understanding of the lncRNA word in various biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics indicate the functional diversity of lncRNAs, which may perform different important physiological regulatory roles in mammary gland development and lactation. Other studies, such as those conducted on bovines, have attempted to identify and characterize the expression of lncRNAs in peak, late and dry lactation stages [23,24], and lncRNAs, as an important posttranscriptional regulators, participate widely in the regulation pathways related to the development and lactation of mammary glands. Therefore, an extensive investigation of the functions of lncRNAs will provideus with a clear understanding of the lncRNA word in various biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs can be either single-exonic or multi-exonic, while it is a challenge to distinguish true lncRNAs from the abundant one exon, low expression fragments and expression noise assembled from RNA-Seq data (Cabili et al 2011;Derrien et al 2012). Thus, we only chose multi-exonic lncRNAs for further analysis, as was done in other studies (Tong et al 2017;Kern et al 2018;Yang et al 2018;Yue et al 2019), and depends on a highly stringent filtering pipeline to minimise the number of false-positive lncRNAs. Consequently, 4155 non-protein coding transcripts were considered as highly reliable lncRNAs, which was less than previous studies due to our stringent criteria (Billerey et al 2014;Liu et al 2017;Choi et al 2019;Yue et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of genetic array and high throughput sequencing technology, more and more lncRNAs have been discovered in human, rat and mouse (Zhao et al 2016). Recently, lncRNAs have also been identified in pig (Yang et al 2017;Jin et al 2018;Kern et al 2018), chicken (Muret et al 2017;Kern et al 2018;Li et al 2019), sheep (Ren et al 2016;Ling et al 2017;Bush et al 2018;Sulayman et al 2019) and cattle (Billerey et al 2014;Koufariotis et al 2015;Tong et al 2017;Bush et al 2018;Kern et al 2018;Weikard et al 2018;Yang et al 2018;Choi et al 2019;Wang et al 2019;Yue et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third study investigated the transcriptomes of goat somatic cells, milk fat globules and blood cells via using microarrays [6]. This situation contrasts strongly with that of cattle, in which several studies outlining how the gene expression profile of the mammary gland changes in response to different experimental conditions have been published so far [7][8][9][10]. Indeed, RNA-Seq studies performed in dairy cattle [11] and also in sheep [12] have revealed that hundreds of genes are differentially expressed (DE) in the mammary gland when lactating vs. non-lactating individuals are compared.…”
Section: Introductionmentioning
confidence: 99%